PENGARUH SURAT TEGURAN, SURAT PAKSA, SURAT PERINTAH MELAKSANAKAN PENYITAAN DAN PENGUMUMAN LELANG TERHADAP PENERIMAAN TUNGGAKAN PAJAK - Rani Febrina; Emrinaldi Emrinaldi; Hariadi Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to examine the influence exhortation letter, force letter, confiscation letter and auction announcement to Disbursement of tax arrears. Object of this research is tax service office primary of Senapelan Pekanbaru. Model analysis of the data used in this research is a descriptive statistics to examine and pass exhortation letter, force letter, confiscation letter and auction letter to the toward disbursement in 2013-2015 in tax service office primary of Senapelan Pekanbaru. The result of this research is exhortation letter has no influence to disbursement of tax arrears with significant is 0,518, force letter has influence to disbursement of tax arrears with significant is 0,039, confiscation letter has influence to disbursement of tax arrears with significant is 0,010 and auction letter has no influence to disbursement with significant is 0,925. The coefficient of determination indicates 0,496 or 49.6%, which means 49.6% disbursement of arrears of taxes affected by the amount of force letter and confiscation letter. Meanwhile, melt the remaining 50.4% of tax arrears is influenced by other factors beyond the scope of this.Keywords: Exhortation Letter, Force Letter, Confiscation Letter And Auction Announcement, Disbursement